2009
DOI: 10.1007/s10072-009-0074-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ginkgolide B in the prophylaxis of migraine with aura

Abstract: In a multicentric, open, preliminary trial, we evaluated the use of ginkgolide B, a herbal constituent extract from Ginkgo biloba tree leaves, in the prophylactic treatment of migraine with aura (MA). Fifty women suffering from migraine with typical aura, or migraine aura without headache, diagnosed according to International Headache Society criteria, entered a six-month study. They underwent a two month run-in period free of prophylactic drugs, followed by a four month treatment period (subdivided into two b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 14 publications
0
26
0
1
Order By: Relevance
“…The efficacy of ginkgolide B was confirmed in preventing migraine with aura [24] and pediatric migraine [25]. From our preliminary experience, the use of ginkgolide B associated with vitamin B2, Coenzime Q10 and Mg, administered from ovulation until the first day of menstruation, is also useful in the prophylaxis of MM, especially if the attacks tend to occur on days -2, -1 and ?1 with respect to the onset of menstruation.…”
Section: Treatment Strategies For MM In the Context Of Pmsmentioning
confidence: 93%
“…The efficacy of ginkgolide B was confirmed in preventing migraine with aura [24] and pediatric migraine [25]. From our preliminary experience, the use of ginkgolide B associated with vitamin B2, Coenzime Q10 and Mg, administered from ovulation until the first day of menstruation, is also useful in the prophylaxis of MM, especially if the attacks tend to occur on days -2, -1 and ?1 with respect to the onset of menstruation.…”
Section: Treatment Strategies For MM In the Context Of Pmsmentioning
confidence: 93%
“…However, it is worth mentioning that proprietary extracts of Ginkgo and its component Ginkgolide B, either alone or in combination with vitamins and minerals, are the subject of an increasing number of interventions in adult and young migraineurs. 23,29,72,73 Their results seem promising, but the variable composition of the treatments, the open-label trial designs, and the small cohort sizes make it difficult to draw any preliminary conclusions. Accordingly, Ginkgo is generally disregarded as a preventive agent for migraine in the guidelines published by the American and European headache associations.…”
Section: Comparison With Other Herbal Productsmentioning
confidence: 99%
“…Indeed, PAF and glutamate, released from platelets and leukocytes in the blood and from the glia in the CNS, may play a role in the occurrence and propagation of SD in the cortex. In addition, one study has shown that Ginkgolide B is useful in the prophylaxis of MwA [12]. On the basis of this evidence, in an open trial we evaluated the possible efficacy of Ginkgolide B in the treatment of acute aura in a group of patients suffering from MwA, considering in particular the effect of the treatment on aura duration.…”
Section: Introductionmentioning
confidence: 99%